Factors associated with intracranial injury in blast-induced traumatic brain injury - Sungkaro, Kanisorn; Tunthanathip, Thara (Thai Journal of Neurological Surgery, 2025)
Background: Blast-induced traumatic brain injury (bTBI) is one of the major causes of death from traumatic brain injury (TBI) in southern Thailand. However, no consensus has been proposed for the indication of cranial computed tomography (CCT) in bTBI. Therefore, this study aimed to identify the factors associated with intracranial injury after CCT. Methods: A retrospective cohort study was performed on patients with bTBI. Clinical and radiologic characteristics were collected. The outcome of the present study was intracranial injury after CCT that included any type of skull fracture, epidural hematoma, subdural hematoma, coup contusion, contrecoup contusion, intraventricular hemorrhage, subarachnoid hemorrhage, or diffuse axonal injury. Binary logistic regression analysis was performed to identify the factors associated with intracranial injury following CCT. Results: There were 80 patients in the present study with a median age of 32.5 years (IQR 19). According to the severity of bTBI, the majority of patients had mild TBI in 66.3% of all cases. Moderate TBI was found in 10%, where 23.8% of the present cohort comprised severe TBI. Therefore, intracranial injuries were found in 62.5% of all cases. Using multiple logistic regression analysis with a backward stepwise procedure, one factor associated with intracranial injury following CCT was the severity of bTBI (OR of moderate TBI 2.9, 95%CI 0.53-15.63 and OR of severe TBI 8.2, 95%CI 1.71-38.99, Reference mild TBI). Conclusion: The severity of bTBI associated with intracranial injury after CCT should be considered for the development of guidelines concerning CCT for implicating mass causality triage and setting priorities for investigation in the future.